2013
DOI: 10.1159/000348440
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Systemic Inflammation Exacerbates Impairment of Hippocampal Synaptic Plasticity in an Animal Seizure Model

Abstract: Objective: To investigate the effects of systemic inflammation in the critical postnatal stages on neurophysiological actions of immune processes and neural plasticity in adult rats after kainic acid (KA)-induced seizures. Methods: To determine changes in hippocampal synaptic plasticity after postnatal central nervous system inflammatory responses and seizure attacks, we performed intraperitoneal injections of lipopolysaccharide (LPS) in postnatal Sprague Dawley rats on day 14 (P14) to induce central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Experimental evidence indicates significant roles for inflammatory and immune mediators in the initiation of seizures and epileptogenesis. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] In particular, cytokines including IL-1b, IL-6, and TNF-a, and Toll-like receptor 4 have been shown to contribute to seizure generation and epileptogenesis. 28,29 In addition to experimental studies using animal models, human clinical studies have demonstrated alterations in the levels of IL-6 in samples from patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence indicates significant roles for inflammatory and immune mediators in the initiation of seizures and epileptogenesis. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] In particular, cytokines including IL-1b, IL-6, and TNF-a, and Toll-like receptor 4 have been shown to contribute to seizure generation and epileptogenesis. 28,29 In addition to experimental studies using animal models, human clinical studies have demonstrated alterations in the levels of IL-6 in samples from patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that seizures can have a profound impact in hippocampal synaptic plasticity (Reid and Stewart, 1997). For instance, recurrent seizures reduce hippocampal LTP and function in rats (Zhou et al, 2007;Chen et al, 2013) whereas febrile seizures in early life enhance hippocampal LTP and decrease LTD) (Notenboom et al, 2010). Additionally, sustained Status Epilepticus (SE) induced by pilocarpine enhances LTP in hippocampal CA1 neurons of rats (Mu¨ller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Transient cytokine release (including IL-1b, TNFb, and IL-6; see Table 1), microglial priming, and astrocyte reactivity are all mechanisms by which early life immune challenges can yield long-lasting effects on seizure threshold. Several other cytokines, chemokines, and (Heida and Pittman, 2005;Vezzani et al, 2008;Chen et al, 2013) Preterm (Dube et al, 2005;Dube et al, 2010;Fukuda et al, 2014;Fukuda et al, 2015;Patterson et al, 2015) Status epilepticus KA kindling; lithiumpilocarpine Rat, p9-15 • Upregulated IL-1b and IL-1R acutely and chronically (to 8 weeks), associated with glial activation (Holmes and Thompson, 1988;Rizzi et al, 2003;Omran et al, 2012 (Fukuda et al, 2007) Viral infection (MIA) Systemic or intracerebral poly I:C administration Mouse, g12-16 • Chronic epilepsy phenotype in offspring prevented by antibodies to IL-1b and IL-6 (when combined) (Pineda et al, 2013) Prenatal (Galic et al, 2008;Chen et al, 2013;Kosonowska et al, 2015) Bacterial infection (meningitis)…”
Section: Discussionmentioning
confidence: 99%
“…This time period coincides with the developmental peak in synaptogenesis and synaptic pruning, yielding considerable changes in neuronal circuitry which likely underlies this critical window of vulnerability. This paradigm has since been used to demonstrate that LPS exposure increases susceptibility to KA-induced seizures at p35, alongside impairments in long-term potentiation and exacerbated hippocampal neurodegeneration (Chen et al, 2013), and pilocarpineinduced seizures at 2 months of age (Setkowicz et al, 2017). In another study, KA was administered simultaneously with LPS to p14 pups, revealing long-lasting molecular changes alongside increased seizure excitability by adulthood.…”
Section: Postnatal Lpsmentioning
confidence: 99%